Answer:
c) (x + 2)(x + 2i)(x - 2i)
Step-by-step explanation:
x^3 + 2x^2 + 4x + 8
= (x^3 + 2x^2) + (4x + 8)
= x^2( x + 2) + 4(x + 2)
= (x + 2)(x^2 + 4)
= (x + 2)(x^2 - 4i^2) ---------------------------->(i^2 = -1)
= (x + 2)(x + 2i)(x - 2i)
Answer:
(- 1, 1 )
Step-by-step explanation:
Given the 2 equations
y = 3x + 4 → (1)
y = x + 2 → (2)
Substitute y = 3x + 4 into (2)
3x + 4 = x + 2 ( subtract x from both sides )
2x + 4 = 2 ( subtract 4 from both sides )
2x = - 2 ( divide both sides by 2 )
x = - 1
Substitute x = - 1 into either of the 2 equations and evaluate for y
Substituting x = - 1 into (2)
y = - 1 + 2 = 1
Solution is (- 1, 1 )
You can apply the Pythagorean theorem:
a^2 + b^2 = c^2
c is the longest side of the triangle
2.2^2 + 4.2^2 = 6.7^2
4.84 + 17.64 = 44.89
22.48 =/= 44.89
That is not a right triangle
Answer:
-11
8 = 2x + 30
8 - 30 = -22
-22 ÷ 2 = -11
x = -11
Also if you place 2×(-11) + 30 you get 8
8 printers for $145 each is a total of $1160.
3 laptops for $439 is a total of $1317.
Therefore, the price of 3 laptops for $439 each cost more than 8 printers for $145 each.